Inoculation with Azospirillum brasilense on corn yield and yield components in an integrated crop-livestock system (Acta Scientiarum. Agronomy, 2018)
Inoculation of corn with diazotrophic bacteria reduces the need for nitrogen fertilization and mitigates environmental contamination risks due to the bacteria’s biological nitrogen-fixation capacity. The aim of the present study was to evaluate the effect of corn seed inoculation with Azospirillum brasilense under different nitrogen levels and post-grazing residual heights. The experiment was performed in two growing seasons and conducted in an integrated crop-livestock system for the 2014/15 and 2015/16. A factorial randomized block experimental design with sub-divided plots and three factors. The main plots varied in post-grazing residual height (0.10, 0.20, 0.30 m, continuous grazing, or no grazing), the subplots varied in inoculation (with or without seed inoculation), and the sub-subplots varied in nitrogen level (0, 75, 150, 225, or 300 kg ha-1 of N). The higher post-grazing residual height associated an A. brasilense and nitrogen fertilization resulted in increased corn biomass and production and yield. At the 300 kg dose of N, the highest grain yield was obtained under different post-grazing heights (10.15 Mg ha-1) and in the absence of the bacterium (10.00 Mg ha-1). Azospirillum brasilense helps plant growth and yield but does not replace the effect of N fertilization.